Investigating The Correlation between EFL Learners’ Level of Critical Thinking and Irony comprehension Case of 3rd year EFL students at M’sila University - Zeyneb MAROUCHE.Hizia AMMARI., Dr. Imane CHERIET (université mohamed boudiaf .m'sila, 2023)
Abstract In today’s complex and interconnected world, effective communication extends beyond mere superficial comprehension, encompassing intricate interpretations and layered meanings. As these meanings intertwine within the multifaceted communication landscape, the exploration of the underlying cognitive processes becomes a captivating avenue of inquiry. On that account, the present study explores the relationship between Algerian EFL learners’ level of critical thinking (CT) and their ability to comprehend irony. In addition, the study investigates EFL teachers’ beliefs and attitudes towards developing CT among students. In order to accomplish these objectives, the researchers opted for a mixed-methods design, combining both correlational and descriptive methods. First, the correlational study is conducted with thirty (30) third year EFL students at M’sila university. In this regard, two data collection tools were used, namely the California Critical Thinking Skills Test (CCTST) and Watson-Glaser Appraisal (WG) as well as Irony Comprehension Test (ICT). As for the descriptive study, data were collected from eight (8) EFL teachers at M’sila university, using a written questionnaire. Through statistical analysis, processed in the Statistical Package for Social Sciences (SPSS) version 24, a strong positive correlation, with a Pearson value of 0.708, is revealed between CT and irony comprehension (IC). Additionally, most teachers stressed the importance of integrating CT in EFL classes. These findings, therefore, underscore the significance of fostering critical thinking skills (CTS) within educational contexts, particularly EFL classrooms, as they positively impact the ability to recognize and effectively interpret ironic elements present in everyday communication.
Keywords: Keywords: Critical Thinking, Critical Thinking Skills, Irony Comprehension, EFL Learners, EFL Teachers.